Beyond Fingal's Cave : Ossian in the Musical Imagination - Porter, James, 1937- (Book collections on Project MUSE., 2019)
Demonstrates the profound impact of The Poems of Ossian on composers of the Romantic Era and later: Beethoven, Schubert, Mendelssohn, Brahms, Massenet, and many others.